Impact of Medical Tourism on Cosmetic Surgery in the United States - Franzblau, Lauren E. (Wolters Kluwer Health, 2013)
SUMMARY: Developing countries have been attracting more international patients by building state-of-the-art facilities and offering sought-after healthcare services at a fraction of the cost of the US healthcare system. These price differentials matter most for elective procedures, including cosmetic surgeries, which are paid for out of pocket. It is unclear how this rise in medical tourism will affect the practice of plastic surgery, which encompasses a uniquely large number of elective procedures. By examining trends in the globalization of the cosmetic surgery market, we can better understand the current situation and what plastic surgeons in the United States can expect. In this article, we explore both domestic and foreign factors that affect surgical tourism and the current state of this industry. We also discuss how it may affect the practice of cosmetic surgery within the United States.